2011
DOI: 10.1371/journal.pcbi.1002265
|View full text |Cite
|
Sign up to set email alerts
|

Speed, Sensitivity, and Bistability in Auto-activating Signaling Circuits

Abstract: Cells employ a myriad of signaling circuits to detect environmental signals and drive specific gene expression responses. A common motif in these circuits is inducible auto-activation: a transcription factor that activates its own transcription upon activation by a ligand or by post-transcriptional modification. Examples range from the two-component signaling systems in bacteria and plants to the genetic circuits of animal viruses such as HIV. We here present a theoretical study of such circuits, based on anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 57 publications
3
71
0
Order By: Relevance
“…These effects result in large variability in the switching times of bistable networks. A recent study showed that, at large effective fold changes, the switching times for an autoregulatory network computed using a stochastic model deviates strongly from the deterministic network, and a significant slowdown is predicted [43]. Thus, it would be interesting to explore the effects of the features of feedback architecture studied here in a stochastic framework especially with regards to switching times.…”
Section: Discussionmentioning
confidence: 99%
“…These effects result in large variability in the switching times of bistable networks. A recent study showed that, at large effective fold changes, the switching times for an autoregulatory network computed using a stochastic model deviates strongly from the deterministic network, and a significant slowdown is predicted [43]. Thus, it would be interesting to explore the effects of the features of feedback architecture studied here in a stochastic framework especially with regards to switching times.…”
Section: Discussionmentioning
confidence: 99%
“…In E. coli , nearly half of the 30 RR transcription factors auto-activate expression of operons encoding themselves [4]. Genetic mechanisms and regulatory features of this feedback control have been explored [4][8] but the potential fitness benefit of TCS autoregulation in environmental adaptation are less examined experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…In E. coli , nearly half of the 30 RR transcription factors auto-activate expression of operons encoding themselves [4]. Genetic mechanisms and regulatory features of this feedback control have been explored [4][8] but the potential fitness benefit of TCS autoregulation in environmental adaptation are less examined experimentally. Positive feedback can lead to an ultra-sensitive switch-like response, an increase of regulatory capacity, a delay of response time, and promotion of a bistable system that can yield all-or-none output [4], [5], [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a single feedback loop to be bistable, its reactions must generate a non-linear switch-like sigmoidal response, termed ultrasensitive response even in the absence of feedback regulation [9][10][11] . In the absence of ultrasensitive reactions, the feedback loop is strictly monostable, and the expression converges to a single steady-state level.…”
Section: Introductionmentioning
confidence: 99%